PERSETUJUAN PEREMPUAN DALAM PERKAWINAN PERSFEKTIF FIKIH DAN UU NO.1 TAHUN 1974 - Shafra, Shafra (Alhurriyah, 2015)
This study aims to analyze the approval of woment in marriage. In the context of Fiqih, the parents in this case, the father has the right to match daughter even she likes it or not. It is mean father has the right to marry their daughter even though the girl is not approval. This right is callad the right of ijbar. in the context of Indonesia under law NO.1 of 1974 concerning marriage ijbar does not know their rights. Father should not marry his daughter except upon approval. This line added to this article in 6 paragraph 1 of th decree No.1 of 1974. From a conduced of this study found that the father’s right to marry his daughter without her consent in the concept of Fikih must meet the following requirements : a harmonious relationship that exists between father and daughter, the couple were chosen for parents commensurate with this daughter, healthy phisycal and economic well established. While the provisions of article 6 paragrafh 1 og the decree No.1 of 1974 about marriage requires the consent of both parties, male and female. The purpose is to fade the gap between then after getting married. In addition. Women todaywas tied by many social factors, so they more courageous and fair to extend their approval for marriage ability or marry.